Journal of Hydroinformatics - Journal of Hydroinformatics (IWA Publishing, 2026)
Publishes original research in hydrology and water management, covering surface and groundwater systems, modeling, infrastructure design, and socio-economic aspects of water resources.
FI 0.59
Q3
Keywords: Physical Sciences & Engineering; Water Resources; Recursos hídricos; Acuerdos transformativos; Transformative agreements; Sistemas hidráulicos; Hidrosistemas; Modelos hidrológicos